Selective laser melting of dense and crack-free AlCoCrFeNi2.1 eutectic high entropy alloy: Synergizing strength and ductility. (1st August 2022) - He, Lin; Wu, Shiwei; Dong, Anping; Tang, Haibin; Du, Dafan; Zhu, Guoliang; Sun, Baode; Yan, Wentao
Highlights: Dense and crack-free EHEA part was fabricated successfully with SLM. The yield strength of the as-SLM part was almost doubled to 982 MPa compared to the as-cast sample. The width and grain morphology in the transition zone were depended on the misorientation between the newly formed and the previous layer. Abstract: Additively manufactured high-entropy alloys generally suffer from low strength and/or poor ductility. In this work, by leveraging the good castability of eutectic high entropy alloys and high cooling rate of selective laser melting (SLM), we report a nearly fully dense and crack-free as-SLM AlCoCrFeNi2.1 eutectic high entropy alloy with an exceptional strength-ductility synergy, showing an ultrahigh yield strength of 982.1 ± 35.2 MPa and an ultimate tensile strength of 1322.8 ± 54.9 MPa together with an elongation to fracture of 12.3 ± 0.5%. Such strength-ductility enhancement is owing to the heterogeneous eutectic microstructure consisting of the columnar, equiaxed, and "L-shape" cells with much refined sizes down to nanoscales. The morphology of cells in the transition zone is related to the misorientation between the growth direction of adjacent layers. This heterogeneous eutectic microstructure is the result of the grain-growth behavior dominated by the mechanisms of the epitaxial growth and growth of heterogeneous nuclei in SLM. Our current results provide a new methodology for the future design of ultrahigh-strength and ductile SLM-fabricated metallic materials including HEAs, and other printable alloys for various structural applications.